2018
DOI: 10.1038/cmi.2018.5
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive STAT3 phosphorylation and IL-6/IL-10 co-expression are associated with impaired T-cell function in tuberculosis patients

Abstract: T-cells critically contribute to protection against Mycobacterium tuberculosis infection, and impaired T-cell responses can lead to disease progression. Pro-inflammatory and immunosuppressive cytokines affect T-cells, and fine-tuned regulation of cytokine signaling via the Jak/STAT signaling pathways is crucial for appropriate T-cell function. Constitutive STAT3 phosphorylation as a consequence of aberrant cytokine signaling has been described to occur in pathognomonic T-cell responses in inflammatory and auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
59
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 59 publications
8
59
1
Order By: Relevance
“…Hydrostatin-SN10 treatment significantly reduced the number of apoptotic cells via the inhibition of the IL-6 and protein levels of proapoptotic biomarkers, such as caspase 3 and BAX, and increase of antiapoptotic biomarkers Bcl2 (Figures 4, 6, and 8). Previous studies have shown that IL-6 restores the phosphorylation of STAT3 [28], thereby promoting the apoptosis of lung cells, and our present findings was consistent with the reports.…”
Section: Discussionsupporting
confidence: 93%
“…Hydrostatin-SN10 treatment significantly reduced the number of apoptotic cells via the inhibition of the IL-6 and protein levels of proapoptotic biomarkers, such as caspase 3 and BAX, and increase of antiapoptotic biomarkers Bcl2 (Figures 4, 6, and 8). Previous studies have shown that IL-6 restores the phosphorylation of STAT3 [28], thereby promoting the apoptosis of lung cells, and our present findings was consistent with the reports.…”
Section: Discussionsupporting
confidence: 93%
“…We next examined the molecular mechanisms by which IL6 promotes glioma cancer stemness. Previous studies have clearly shown that IL6 exerts its effects through the JAK1-STAT3 signal transduction pathway [30][31][32]. Similarly, we observed that the phosphorylation of STAT3 (p-STAT3) was activated in the IL6 recombinant protein treatment in glioma cells ( Figure 5F).…”
Section: Il6 Promotes Glioma Cancer Stemness Via Stat3 Activationsupporting
confidence: 80%
“…However, intracellular IFN-γ measurements in purified PBMCs largely reversed impaired T-cell response to PHA in tuberculosis patients, indicating that serum factors at least partially accounted for impaired PHA induced T-cell response. A possible explanation would be high levels of inflammatory and regulatory cytokines found in serum of patients with acute tuberculosis (26, 27). Recently, we showed that high serum IL-10 and IL-6 levels were accompanied by constitutive STAT3 phosphorylation and SOCS3 expression (27).…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation would be high levels of inflammatory and regulatory cytokines found in serum of patients with acute tuberculosis (26, 27). Recently, we showed that high serum IL-10 and IL-6 levels were accompanied by constitutive STAT3 phosphorylation and SOCS3 expression (27). Especially SOCS3 correlated negatively with T-cell IFN-γ production and may therefore contribute to low PHA response (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation